National unity: a systematic review from the perspective of policy effectiveness experience - Kang, Hongpeng; Fee, Lee Yok; Ku Samsu, Ku Hasnita; Ismail, Mohd. Mahadee (EnPress Publisher, 2024)
National unity is a matter of great concern for many countries around the world today. The study of policy evaluation is an important aspect of the study of national unity. The evaluation of policy implementation effects can help policymakers analyze whether there are problems in the formulation and implementation of the policy, thereby promoting further policy adjustments to better achieve national unity. This article adopts thematic searches and a systematic literature review as research methods. Through the systematic review, it summarizes and analyzes the research on national unity policies across different regions and countries. The article has two objectives: First, to explore the current perspectives in the research on national unity policies, and second, to analyze the state of research regarding the effectiveness of national unity policies. Among the 35 papers analyzed, 7 were on integration policy, 6 were on education policy and 4 were on language policy. To a certain extent, this reflects the perspectives of some countries in Europe, Asia and Africa, including France, Greece, Russia, Turkey, China, Sri Lanka, Nepal, Kenya, South Africa, Nigeria and other countries on the governance of national unity. Research on policy effectiveness is mainly conducted from the perspectives of policy content and policy implementation. However, there is little analysis of successful cases that achieved the desired goals. The main contributions of this article are as follows: first, it summarizes and identifies the characteristics of national solidarity-related policies in different continents and countries. Secondly, the experience of the success and failure of the national unity policy is studied and summarized. In addition, this article also found that there are still gaps in the research on successful experiences and causes.